2013
DOI: 10.1002/maco.201307331
|View full text |Cite
|
Sign up to set email alerts
|

The hot corrosion behavior of plasma sprayed zirconia coatings stabilized with yttria, ceria, and titania in sodium sulfate and vanadium oxide

Abstract: This paper compares the hot corrosion performance of yttria-stabilized zirconia (Zirconia-3-4Yttria, YSZ), ceria stabilized zirconia (Zirconia-24Ceria-2.5Yttria, CSZ), and titania stabilized zirconia (Zirconia-18Titania-10Yttria, TiSZ) coatings in the presence of molten mixture of sodium sulfate þ vanadium oxide at 1050 8C. These coatings were prepared by air plasma spray (APS). Characterizations using X-ray diffraction (XRD) and scanning electron microscope (SEM) indicate that in the case of YSZ, the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Fe gets oxidized in the presence of O to form Fe 2 O 3 oxide layer. Habibi and Guo (2015) and Katiki et al (2014) also observed similar outcomes at elevated temperature in the molten salt environment.…”
Section: Discussionmentioning
confidence: 62%
“…Fe gets oxidized in the presence of O to form Fe 2 O 3 oxide layer. Habibi and Guo (2015) and Katiki et al (2014) also observed similar outcomes at elevated temperature in the molten salt environment.…”
Section: Discussionmentioning
confidence: 62%
“…Its unique crystal structure also allows for the formation of epitaxial thin films, which can further enhance its performance as a TBC material. The use of LaAlO 3 in TBCs has shown promising results, with improved thermal barrier performance and increased durability under hightemperature and thermal cycling conditions [61].…”
Section: Lanthanum Aluminate (Laalo 3 )mentioning
confidence: 99%
“…The tests reported in the literature have been conducted from 700 o C to about 1050 o C using different salt concentrations, with a majority of the tests focused on YSZ thermal barrier coatings. Limited research on the corrosion mechanism of other top coat materials such as gadolinium zirconate [48,49,55], ceria-stabilized zirconia [56][57][58], titaniastabilized zirconia [58], scandia and yttria co-stabilized zirconia [59] and zirconia-alumina [54] have been reported as well.…”
Section: Hot Corrosion Tests -Failure Mechanismsmentioning
confidence: 99%